Devoid Elites and the Need for a New Elite Configuration: An Analysis of Post-Soviet Societies on the Example of Azerbaijan - Gerlich, Michael (Journal of Ethnic and Cultural Studies, 2023)
This paper provides a comprehensive study of the Azerbaijani ruling elites. This study aims to describe the post-Soviet Azerbaijani elites, their interaction, and their influence to elaborate a basis for studying the impact on the government and the economy. The study focuses on the definition and origin of the Azerbaijani elites after the collapse of the Soviet Union, the analysis of their interactions, and the definition of behavior and hierarchy. The study relies on Higley and Burton’s (2006) elite configurations framework and Wedel’s (2003) concept of clans. It draws on qualitative analysis and applies analytical autoethnographic approaches to analyze and interpret the information received. The study used data from 113 informal dialogue interviews with those who worked closely with the elite and the elite representatives. These data provided detailed descriptions of their life and behavior in Central Asia and the South Caucasus. The total number of respondents was 1,817 people. Not all elites have equal access to power. Some, called “hyperagents,” control most decisions. Others, whom the author defines as “devoid elites”, have very little or no real power, although they have some privileges that the elites are endowed with in society. The researcher proposes a new elite configuration entitled “imposed unity elites”, which better describes the majority of Azerbaijani elites. This elite configuration implies the existence and behavior of devoid elites. It also describes elites that seem to be united in public but lacks any basic ideology or common goals. The research contributes to the further development of Higley and Burton’s (2006) framework of elite configurations and the theory of the influence of elites. The possible application of the obtained research results will allow scientists to better understand the development characteristics of the elite configuration in the post-Soviet space and their impact on the state.